HUBUNGAN LAMA BERKENDARA DENGAN KELUHAN NYERI LEHER PADA MAHASISWA UPN "VETERAN" JAKARTA - Wulandari Nofitri (2023)
Background : Driving in a big city with a high level of congestion can extend driving time and long distances can be classified as repetitive work which has the potential to cause complaints of neck pain. Neck pain is the fourth leading cause of disability with point prevalence ranging from 5.9% to 38.7%. The high frequency of motorcycle riders who are exposed to discomfort while driving causes musculoskeletal symptoms in their body parts. Various Musculoskeletal complaints that can arise such as pain in the neck, shoulders, spine, lower back, wrists and fingers to pain in the ankles. Research Objectives : relationship between prolonged driving on musculoskeletal complaints (neck pain) in college students. Research Method : This study used a cross-sectional method. With a sample of 231 students who ride motorcycles, this research was conducted using a questionnaire with the NDI (Neck Disability Index measurement tools. Results: The correlation test in this study from the Spearman correlation test obtained a value of p = 0.039 (<0.05) and the value of the correlation coefficient on driving duration was worth r = 1 and complaints of neck pain were worth r = 0.136. This indicates that there is a relationship between driving duration and complaints of neck pain in the weak level category.